Pengaruh Pecahan Genteng dan Keramik sebagai bahan Pengganti Semen terhadap Kuat Tekan - Rosalia, Devi; Purnomo, Julyan; Aida, Nur (Teknik Sipil, Politeknik Negeri Ketapangg, 2025)
In a construction project, roof tiles and ceramics that are cracked (broken) are often thrown away as construction waste. Apart from that, house demolition activities also produce roof tile and ceramic shards that are not reused. No one has conducted research where this wastes is used as a substitute for cement. This research aims to determine the effect of roof tile and ceramic fragments as a substitute for cement on the compressive strength value of concrete. Experimental methods were used in this research. Observations were carried out at the structure and materials laboratory, Ketapang State Polytechnic. The results of the research show that the effect of using tile and ceramic fragments as a substitute for cement with varying percentages of 5% tile, 5% ceramic, 5% tile and ceramic, and 10% tile and ceramic in concrete has an effect on the compressive strength value. The greater the percentage of tile and ceramic fragments used in the concrete mixture, the more the compressive strength value of the concrete will decrease. The average compressive strength of concrete at 7 days between normal concrete and concrete with varing percentages of 5% tile, 5% ceramic, 5% tile and ceramic, and 10% tile and ceramic has a comparative value of 12.76 M.Pa, 12.03 MPa, 12.16 MPa, and 11.03 MPa. The average estimated compressive strength of concrete aged 28 days has comparative values of 19.00 MPa, 18.51 MPa, 18.71 MPa, 17.43 MPa, and 16.97 MPa.